2011
DOI: 10.1002/lary.21401
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of postinfectious olfactory disorders with minocycline: A double‐blind, placebo‐controlled study

Abstract: In conclusion, the present results indicate that minocycline in the given dosage has little or no effect on the recovery of human olfactory function following postinfectious olfactory loss. However, spontaneous recovery is found in approximately 20% of the patients over an observation period of 7 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 22 publications
2
52
1
1
Order By: Relevance
“…Due to high rates of spontaneous improvement of PIOD, any successful treatment must generate beneficial effects that occur more frequently than spontaneous recovery. Spontaneous remission rates were reported to vary from 6% to 67% in the literature, depending on the duration of follow up . The rates of spontaneous remission of PIOD gauged by validated smell tests in previous series (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Due to high rates of spontaneous improvement of PIOD, any successful treatment must generate beneficial effects that occur more frequently than spontaneous recovery. Spontaneous remission rates were reported to vary from 6% to 67% in the literature, depending on the duration of follow up . The rates of spontaneous remission of PIOD gauged by validated smell tests in previous series (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Significant improvement was defined as improvement in more than 20% of participants (double the rate of spontaneous remissions within 16 weeks). A clinically significant improvement of TDI scores was defined by an increase of at least six points …”
Section: Methodsmentioning
confidence: 99%
“…For postviral and posttraumatic olfactory loss several treatments have been suggested [for an overview, see [54,86]]. Zinc [87,88], vitamin A [89], and the antibiotic minocycline [90] have been shown to be ineffective in placebo-controlled studies. α-lipoic acid [91] and the phosphodiesterase inhibitors theophylline [92,93] and pentoxifylline [94] have not been tested in placebo-controlled studies yet.…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model of head trauma, the anti-inflammatory/anti-apoptotic agent minocycline showed promise at preventing olfactory loss, if administered at the time of damage [39]. However, studies so far have not shown efficacy in humans [40]. Novel drugs, perhaps aimed at reducing degeneration or preventing glia scar formation, are needed.…”
Section: Disorders Of Olfactory Neuron Maintenancementioning
confidence: 99%